Wetland degradation promotes soil P fraction transformation by altering P-cycling functional genes and metabolic pathways - Jiang, Yumeng; Zou, Yu; Sun, Miaojia; Zhu, Weihong; Xu, Wanling (Frontiers in Microbiology, 2025)
Global wetlands have undergone varying degrees of degradation due to intense disturbances from global climatic and environmental changes, and human activities such as overgrazing and drainage. While wetland degradation is known to alter soil physicochemical properties and phosphorus (P) cycling, the mechanism governing its effects on soil P fraction transformation and P metabolism remains poorly understood. To address this, we investigated how different stages of wetland degradation—non-degraded (ND), slightly degraded (LD), moderately degraded (MD), and heavily degraded (HD)—affect soil P fractions in temperate wetlands. We analyzed soil properties, P-cycling microbial communities, functional genes, and metabolic products, employing the modified Hedley P fractionation method to elucidate clear trends in P fraction contents. Our results show that total inorganic P content decreased significantly with increasing degradation intensity. Specifically, labile Pi (Resin-Pi and NaHCO₃-Pi), mod-labile Pi (NaOH-Pi), and stable Pi (1 M HCl-Pi and Residual-P) all declined significantly, although Conc. HCl-Pi exhibited an initial decrease followed by an increase. In contrast, total organic P content increased, with significant increases in labile Po (NaHCO3-Po) and mod-labile Po (NaOH-Po), while stable Po (Conc. HCl-Po) decreased markedly. These shifts indicate that wetland degradation promotes the interconversion among labile P, mod-labile P, and stable P forms. The degradation process is initiated by a reduction in soil moisture, which subsequently regulates soil pH and other physicochemical properties. These changes further drive shifts in microbial community diversity, influence the abundance of P-cycling functional genes, and alter P metabolic pathways, ultimately affecting both the speciation and total pool of soil phosphorus. The accumulation of labile Po is primarily attributed to the obstruction of mineralization, resulting from the reduction of terminal functional genes in the Po mineralization pathway. These findings enhance our understanding of P-cycling mechanisms in degraded wetlands and provide a theoretical basis for phosphorus management during wetland restoration efforts.